The Role of Parents' Interpersonal Communication in Accompanying Children with use Gadgets - Huda, Nurul; Aristawati, Evy; Cahyono, Bagus Dwi (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Children are God's gift in marriage. Child development is the responsibility of parents. During the current development period, children will face increasingly modern times with increasingly sophisticated technology with the use of gadgets, this condition has an impact on changes in activities where they spend more time playing with gadgets. Regarding the use of gadgets by children, the role of parents is important to see this as the background and formulation of the problem created is "What is the role of parents' interpersonal communication in accompanying children to use gadgets?". This research aims to determine the role of parent-child communication in accompanying children to play gedget which contains positive and good things to do in Pasuruan, East Java. The method used is a qualitative descriptive method. The data obtained was analyzed qualitatively and presented in the form of detailed and systematic descriptions. The research results show that interpersonal communication plays an important role in harmonious family relationships. Through interpersonal communication, parents act as teachers and friends for children. This role is an effort to teach education to children through technological developments. the scheme of relationships within the family and the interactions that occur in the form of supervision and control of children. How does the communication relationship between parents and children influence the final results of the use of gadgets taught by parents to children.